Interleukin-27-induced HIV-resistant dendritic cells suppress reveres transcription following virus entry in an SPTBN1, autophagy, and YB-1 independent manner. - Tomozumi Imamichi; Qian Chen; Bharatwaj Sowrirajan; Jun Yang; Sylvain Laverdure; Mayra Marquez; Anthony R Mele; Catherine Watkins; Joseph W Adelsberger; Jeanette Higgins; Hongyan Sui (PLoS ONE)
Interleukin (IL)-27, a member of the IL-12 family of cytokines, induces human immunodeficiency virus (HIV)-resistant monocyte-derived macrophages and T cells. This resistance is mediated via the downregulation of spectrin beta, non-erythrocytic 1 (SPTBN1), induction of autophagy, or suppression of the acetylation of Y-box binding protein-1 (YB-1); however, the role of IL-27 administration during the induction of immature monocyte-derived dendritic cells (iDC) is poorly investigated. In the current study, we investigated the function of IL-27-induced iDC (27DC) on HIV infection. 27DC inhibited HIV infection by 95 ± 3% without significant changes in the expression of CD4, CCR5, and SPTBN1 expression, autophagy induction and acetylation of YB-1 compared to iDC. An HIV proviral DNA copy number assay displayed that 27DC suppressed reverse transcriptase (RT) reaction without influencing the virus entry. A DNA microarray analysis was performed to identify the differentially expressed genes between 27DC and iDC. Compared to iDC, 51 genes were differentially expressed in 27DC, with more than 3-fold changes in four independent donors. Cross-reference analysis with the reported 2,214 HIV regulatory host genes identified nine genes as potential interests: Ankyrin repeat domain 22, Guanylate binding protein (GBP)-1, -2, -4, -5, Stabilin 1, Serpin family G member 1 (SERPING1), Interferon alpha inducible protein 6, and Interferon-induced protein with tetratricopeptide repeats 3. A knock-down study using si-RNA failed to determine a key factor associated with the anti-HIV activity due to the induction of robust amounts of off-target effects. Overexpression of each protein in cells had no impact on HIV infection. Thus, we could not define the mechanism of the anti-HIV effect in 27DC. However, our findings indicated that IL-27 differentiates monocytes into HIV-resistant DC, and the inhibitory mechanism differs from IL-27-induced HIV-resistant macrophages and T cells.